The Meaning of Going Concern Based on the Awareness of Micro, Small and Medium Enterprises (MSMEs) - Putri, Shermaliana; Sokarina, Ayudia (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to interpret the meaning of going concern based on the awareness of Micro, Small and Medium Enterprises (MSMEs). This research is a qualitative research with an interpretive and phenomenological paradigm as a research methodology. The data collection techniques in this study are interviews and documentation. The informants of this study are two going concern is not only interpreted through financial aspects, but also through religious and cultural aspects in the form of sincerity, resignation, and obedience to religious provisions and belief that the sustainability of business brings blessings from God. This is the power that allows micro business actors to survive in the midst of difficult conditions. The implications of this study can provide a new perspective to business actors regarding the meaning of going concern so that they can continue to develop and maintain their business operations.